2022
DOI: 10.21037/atm-22-450
|View full text |Cite
|
Sign up to set email alerts
|

Messenger RNA expression profiles and bioinformatics analysis of mouse hippocampi during exercise alleviates methamphetamine dependence via mRNA profile change in hippocampi

Abstract: Background: Methamphetamine (METH) is a highly addictive, psychoactive drug which can harm individual health and lead to great social problems. Various approaches have been adopted to address the problems arising from METH addiction, but relapse rates remain high. Recently, it has been found that comprehensive treatment combined with scientific and appropriate exercise interventions can improve the mental state and physical fitness of drug addicts and promote their physical and mental rehabilitation. Long-term… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…Moreover, we additionally found that METH markedly disturbed the expression of the genes associated with cell cycle progression, which resulted in cell cycle arrest and eventually led to abnormalities in both differentiation and migration of neurospheres. Although the screened DEGs in this study were differently changed compared to the reported DEGs in METH-treated hippocampus in vivo ( Zoubková et al, 2019 ; Li et al, 2022 ), the identified DEGs in neurospheres were not only validated by the qRT-PCR but the DEGs-enriched cell signaling was also investigated, demonstrating the critical role of altered genes in METH-caused toxicity. Hence, our findings shed light on the mechanisms underlying METH-induced neurodevelopmental deficits.…”
Section: Discussionmentioning
confidence: 64%
“…Moreover, we additionally found that METH markedly disturbed the expression of the genes associated with cell cycle progression, which resulted in cell cycle arrest and eventually led to abnormalities in both differentiation and migration of neurospheres. Although the screened DEGs in this study were differently changed compared to the reported DEGs in METH-treated hippocampus in vivo ( Zoubková et al, 2019 ; Li et al, 2022 ), the identified DEGs in neurospheres were not only validated by the qRT-PCR but the DEGs-enriched cell signaling was also investigated, demonstrating the critical role of altered genes in METH-caused toxicity. Hence, our findings shed light on the mechanisms underlying METH-induced neurodevelopmental deficits.…”
Section: Discussionmentioning
confidence: 64%
“…In another study, Li et al demonstrate that mice subjected to treadmill running have reduced addiction to methamphetamine. Using RNA‐seq, they show that the a number of genes are differentially regulated between running and sedentary mice given methamphetamine (Li et al, 2022).…”
Section: Molecular Mechanisms Underlying Enhanced Adult Hippocampal N...mentioning
confidence: 99%
“…In another study,Li et al demonstrate that mice subjected to treadmill running have reduced addiction to methamphetamine. Using RNA-seq, they show that the a number of genes are differentially regulated between running and sedentary mice given methamphetamine(Li et al, 2022).McGreevy et al have investigated the heritability of the impact of physical exercise from father to offspring. They show that increased adult neurogenesis, greater mitochondrial citrate synthase activity, and paternal cognitive improvements of the runner-fathers can be inherited by their offspring.…”
mentioning
confidence: 99%
“…There is extensive work in the literature ( Centanni et al, 2022 ; Li et al, 2022 ; Re et al, 2022 ) demonstrating that exercise can improve withdrawal symptoms and reduce relapse rates. Therefore, exercise has been considered an excellent adjunct treatment to existing treatment regimens ( Wang et al, 2014 ; He et al, 2021 ; Salem et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%